The influence of brand marketing on consumers’ emotion in mobile social media environment - He, Xingjie; Zhu, Lixiao; Sun, Lin; Yang, Linqian (Frontiers in Psychology, 2022)
With the development of urban economy and the enhancement of competition among cities, urban marketing has attracted more and more attention. Emotional marketing is a people-oriented marketing strategy, which can not be ignored under the current economic development and urban development level. Today, with abundant commodities and diversified shopping channels, how to attract new customers, maintain old customers and enhance customer loyalty through emotional marketing has become the focus of enterprises' work. This paper studies from the perspective of clothing. Facing the fierce market competition, in the marketing era of domestic and foreign big enterprises seeking development by brands, if small and medium-sized enterprises want to survive and develop, they must set up the lofty goal of becoming big enterprises, implement brand marketing, and constantly grow and grow healthily in the process of building strong brands. It can be seen from the research in this paper that the recommendation success of this algorithm is 19% better than that of the traditional algorithm in the case of a certain number of partitions, and it is suitable for being put into extensive practice.